Analyzing the Model of Demand and Supply of Labor Post- Coronavirus Disease 2019 (COVID-19) in Luang Prabang City - SIPHANTHONG, Bounthavy; SIOUDOMPHAN, Soutthavone; SENGDARA, Chansamone; KEODUANGKHAM, Phavone; CHITTAPONE, Namfonh (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This scientific research has been conducted under the title “Analyzing the Model of Demand and Supply of Labor Post- Coronavirus Disease 2019 (COVID-19) in LuangPrabang City," which includes 2 study objectives: 1) Analyzing the Model of Demand of Labor Post- Coronavirus Disease 2019 (COVID-19) in LuangPrabang City. 2) Analyzing the Model of Supply of Labor Post- Coronavirus Disease 2019 (COVID-19) in LuangPrabang City. Data collection tools are questionnaires and interviews using SPSS Version 23 to calculate the necessary statistical values and parameter values in the multiple regression equation. The results of the research found that the model of willingness to work and supply of labor is based on the basic factors of labor such as gender, age, status, education level, specialization, and special abilities that affect the demand and supply of labor entering the labor market. It can be seen from the modified decision coefficient value of 0.0960, which means that the factors of willingness to labor contained in the model can explain the change in demand for labor entering the labor market by 9.60% and the remaining part depends on other factors or other independent variables that are not included in the study. Therefore, it can be said that the model is economically feasible and consistent with economic theory. At the same time, the analysis results also show that the probability value of F-stat = 8.166 means that the independent variables included in the model are appropriate and have a statistical significance level of 0.01. While the labor supply model entered the labor market, it can be seen from the modified decision coefficient value of 0.0900, which means that the variables used in the model can explain the change in labor supply by 9.0% and the remaining part depends on other factors that are not included in the study. Therefore, it can be said that the model is economically feasible and consistent with economic theory. In addition, the analysis results also show that the probability value of F-statistics = 7.582 means that the independent variables included in the model are appropriate and have a statistical significance level of 0.01.